The Role of Tanycytes in the Hypothalamus-Pituitary-Thyroid Axis and the Possibilities for Their Genetic Manipulation - Müller-Fielitz, Helge; Schwaninger, Markus (Experimental and Clinical Endocrinology & Diabetes, 2019)
Thyroid hormone (TH) regulation is important for development, energy homeostasis, heart function, and bone formation. To control the effects of TH in target organs, the hypothalamus-pituitary-thyroid (HPT) axis and the tissue-specific availability of TH are highly regulated by negative feedback. To exert a central feedback, TH must enter the brain via specific transport mechanisms and cross the blood-brain barrier. Here, tanycytes, which are located in the ventral walls of the 3rd ventricle in the mediobasal hypothalamus (MBH), function as gatekeepers. Tanycytes are able to transport, sense, and modify the release of hormones of the HPT axis and are involved in feedback regulation. In this review, we focus on the relevance of tanycytes in thyrotropin-releasing hormone (TRH) release and review available genetic tools to investigate the physiological functions of these cells.
Keywords: tanycytes; TRH; HPT axis; genetic tools; viral vectors; transgenic mice